Determining the Elements of Exterior Orientation in Aerial Triangulation Processing Using UAV Technology - Damian Wierzbicki; Kamil Krasuski (Communications - Scientific letters of the University of Zilina, 2020)
Unmanned Aerial Vehicles (UAVs) are still an interesting and current research topic in photogrammetry. An important issue in this area is determining the elements of exterior orientation of image data acquired at low altitudes. The article presents selected mathematical methods (TGC, TIC, TAD) of estimating elements of exterior orientation for image data obtained at low altitudes. The measurement data for the experimental test were recorded by the Unmanned Aerial Vehicle platform Trimble UX-5. In the framework of the test photogrammetric flight, the authors obtained 506 images and navigation data specifying the position and orientation of the Unmanned Aerial Vehicle. As a result of the research, it is proven possible to show the usefulness of the mathematical models (TGC, TIC, TAD) in estimation of elements of exterior orientation.